Understanding Library Users via Surveys and Other Methods—Best Practices for Evidence-Based Library Development. Issue 8 (16th November 2020) - Carlsson, Håkan; Torngren, Tore
Abstract: A survey was performed over all university libraries within the Association of European Research Libraries (LIBER) in order to study how different methods of user input are utilized. Libraries using analysis based on explorative methods—such as UX and process mapping—report significantly increased user knowledge and perceived well-function. Over three-fourths of the respondents reported performing general user surveys. Surveys offer ease of collection, effectively gather researcher user group input and generate data suitable for communicating library value to stakeholders. However, it is resource-demanding to transfer findings into service changes, especially for smaller libraries, and results often support stepwise improvements rather than discovery of new services.